2020
DOI: 10.1002/ajpa.24111
|View full text |Cite
|
Sign up to set email alerts
|

Gendered division of labor in a Celtic community? A comparison of sex differences in entheseal changes and long bone shape and robusticity in thepre‐Romanpopulation of Verona (Italy, third–first centuryBC)

Abstract: Objectives: The presence of a gendered subdivision of labor has been bioarchaeologically investigated in various prehistoric and historical contexts. Little is known, however, about the type of differences in daily activities characterizing men and women among the Celtic communities of Italy. The focus of the present study is the analysis of differences in patterns of entheseal changes (ECs) and long bone shape and robusticity between sexes among the Cenomani Gauls of Seminario Vescovile (SV-Verona, Italy, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 152 publications
(252 reference statements)
0
28
1
1
Order By: Relevance
“…These physical changes have been also pointed out regarding the indigenous remains of Tenerife (Estévez‐González, 2005) and Gran Canaria (Santana‐Cabrera & Moreno‐Benítez, 2014). Nevertheless, our results do not fit a social behaviour where both sexes where involved in completely different tasks (Laffranchi et al, 2020). Conversely, this pattern could reflect the activities of an agropastoral society that required men and women to participate in a wide range of labours with habitual mobility in a rugged landscape.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…These physical changes have been also pointed out regarding the indigenous remains of Tenerife (Estévez‐González, 2005) and Gran Canaria (Santana‐Cabrera & Moreno‐Benítez, 2014). Nevertheless, our results do not fit a social behaviour where both sexes where involved in completely different tasks (Laffranchi et al, 2020). Conversely, this pattern could reflect the activities of an agropastoral society that required men and women to participate in a wide range of labours with habitual mobility in a rugged landscape.…”
Section: Discussioncontrasting
confidence: 87%
“…However, the results in EC and CSG do not allow us to identify a pattern of unilateral activities since there were also high frequencies of enthesis related to activity of specific muscles of the left side. The data indicating biomechanical load exerted by the left limb may be interpreted as the result of the execution of constant bilateral practices, generally more numerous in prehistoric populations (Eshed, Gopher, Galili, & Hershkovitz, 2004; Laffranchi et al, 2020; Lieverse, Bazaliiskii, Goriunova, & Weber, 2009; Santana‐Cabrera, 2011). This bilateral pattern could be used in many complementary activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these evolutionary studies clearly demonstrate a general decrease or changes in skeletal robusticity over time correlated with subsistence mobility or technological innovation, without sufficient sample sizes and wider range of age distributions, they are not able to detect or make meaningful interpretations of age‐ or sex‐related bone loss. However, recent comparative studies of cortical long bone robusticity in a variety of modern populations have found varying patterns of sexual dimorphism that have been suggested to reflect differences in gendered activities and behavior (Laffranchi et al, 2020; Saers et al, 2017; Temple et al, 2021; Zelazny et al, 2021). While these studies do not consider age‐related changes and/or do not have sufficient sample sizes to do so, they do underscore the plasticity of bone morphology with behavior/lifestyle and do not support the “mismatch” hypothesis that females in modern human populations are predestined to have less robust bones or bone fragility.…”
Section: Variation and Plasticity: The Archeological Perspectivementioning
confidence: 99%